Collaborative learning approach to teach computer coding in informal spaces. (2nd January 2022) - Chang-Tik, Chan; Dhaliwal, Jasbir
ABSTRACT: This study examines the participation of the Less Effective Learning Group(LELG) students in Collaborative Learning in Informal Space (CLIS) to gain more insights in two of the five principles of the Framework of Participation. Their participation is based on relationships of mutual recognition and acceptance and participation requires learning to be active and collaborative.Of note, the LELG students focus more on individual work and less on group discussion and the informal learning space includes both the physical and virtual spaces without the presence of a lecturer. The study aims to contribute new pedagogical practices to the framework that are suitable for the LELG students. The research involved 90 Information Technology undergraduates. Data gathered through semi-structured focus group interview were analysed deductively with predetermined codes using the conceptual content analysis. The findings emphasise the importance of teaching LELG students' self-regulation and the appreciation of interdependence that implies accepting theirpeers' views and also defending their contributions. To co-construct knowledge effectively in a collaborative manner they have to regulate their cognitive processes. The pedagogical proposals include promoting group co-regulation and teaching students how to collaborate effectively.